Application of Eco-Drainage Concepts to Mitigate Flood Problems on Jalan Panjang Jiwo, Surabaya - Srinovita, Astria; Saves, Faradlillah (Civil and Sustainable Urban Engineering, 2025)
Rapid population growth in Surabaya has been accompanied by various environmental challenges, one of which was flooding on Jalan Panjang Jiwo. In addition to high rainfall intensity, the city’s flat topography and its location in the downstream area of the Brantas Watershed contributed to the occurrence of flooding. Land conversion into built-up areas also led to a reduction in natural infiltration areas, resulting in increased surface runoff. Furthermore, the suboptimal performance of the existing drainage system made it unable to adequately convey rainwater discharge during periods of high rainfall intensity. This study aimed to examine the potential application of the eco-drainage concept through the injection well method as an alternative flood control measure in the Jalan Panjang Jiwo area. Injection wells were selected because this design was intended to support the infiltration process by allowing rainwater to pass through impermeable or low-permeability topsoil layers. Unlike natural infiltration systems, which relied solely on surface soil permeability, injection wells enabled water to penetrate these layers and reach more permeable soil strata below. Therefore, this method was considered effective for application in urban areas dominated by built-up surfaces with limited green open spaces. The analysis was conducted using hydrological and hydraulic approaches, supported by modeling with EPA SWMM 5.2. Through a trial-and-error process involving calculation and design evaluation, an optimal injection well design with a diameter of 3.25 meters and a depth of 25 meters was obtained. Based on flood discharge estimates under existing channel conditions, a total of six injection wells were required to accommodate surface runoff. The results of this study were expected to serve as technical recommendations for the development of sustainable urban drainage systems, particularly in flat areas with high runoff levels such as Surabaya.